2010
DOI: 10.1080/00103624.2011.528490
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar-Applied Humic Acid to Dry Weight and Mineral Nutrient Uptake of Maize under Calcareous Soil Conditions

Abstract: Greenhouse research was conducted to determine the effects of foliar application of humic acid on dry matter and some nutrient element uptake of maize grown under calcareous soil conditions. Agricultural lime was used to obtain five calcium carbonate (CaCO 3 ) doses (0, 5, 10 20, and 40%) and three foliar application doses of humic acid (0, 0.1, and 0.2%) sprayed at 20 and 35 days after emergence. Although the dry weight and mineral element uptake of maize were affected negatively, especially at 20 and 40% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 25 publications
6
31
0
7
Order By: Relevance
“…with spraying (H.A). This finding is consistent with studies conducted by Celik et al (2010) explained that humus had beneficial effects on nutrient uptake, transport and availability to maize plant that enhances the maize plant growth. Tables 3 and 6 showed that application of FYM or Microbein combined with studied activators (H.A or F.A) had a significant effects on increasing phosphorus uptake in grains in both seasons under study.…”
Section: і Grain Yield Of Maize As Affected By Inorganic Organic Nisupporting
confidence: 82%
See 3 more Smart Citations
“…with spraying (H.A). This finding is consistent with studies conducted by Celik et al (2010) explained that humus had beneficial effects on nutrient uptake, transport and availability to maize plant that enhances the maize plant growth. Tables 3 and 6 showed that application of FYM or Microbein combined with studied activators (H.A or F.A) had a significant effects on increasing phosphorus uptake in grains in both seasons under study.…”
Section: і Grain Yield Of Maize As Affected By Inorganic Organic Nisupporting
confidence: 82%
“…were found by spraying of H.A in 2014 and 2015 seasons, respectively. Similar results was obtained by Puglisi., et al,(2009) ;Celik et al (2010) and Tahir et al, (2011). They indicated that potassium humate as product of HA increases the release of primary macronutrients (N, P and K).…”
Section: і Grain Yield Of Maize As Affected By Inorganic Organic Nimentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphorus losses were found to be much more dependent on the soil texture and soil phosphorus and humus content (Buciene et al, 2007). Humus has beneficial effects on nutrient uptake, transport and availability to plant and it enhances stress tolerance (Celik et al, 2010). In Lithuania, artificial drainage is a common agricultural practice.…”
Section: Introductionmentioning
confidence: 99%